Implementation of the Criminal Law on Illegal Mining to Protect the Wetland Environment in Central Kalimantan Province - Budhi Widodo (International Proceeding On Religion, Culture, Law, Education, And Hindu Studies, 2024)
Climate change has a negative impact on life and is becoming a global problem. The importance of the protection and conservation of wetlands has been agreed in the Ramsar Convention to address carbon emissions. The Indonesian government through the Ministry of Environment and Forestry will “Net Zero Emission” by 2060. This empirical normative research aims to understand the causes, effects, efforts and legal sanctions of perpetrators of illegal mining crimes in wetlands in Central Kalimantan Province. The results of the research conclude that there are still illegal mining crimes due to factors: economics, minimal employment, low legal awareness and working skills. Impact of illegal mining: environmental damage, social problems, triggering potential horizontal conflict and others. Efforts to tackle illegal mining crime are conducted preventively and repressively, but have not effectively resolved the problem. There is a need for decisive action and resolution of problems from the parties involved in the illegal mining issue in accordance with the Mineral and Coal Act. However, the state must continue to strive for the well-being of the people in accordance with the Constitution of UUD NRI of 1945.